Double‐blinded, randomized, and controlled study on the effects of canagliflozin after bariatric surgery: A pilot study - Sangeeta R. Kashyap; Karim Kheniser; Ali Aminian; Philip Schauer; Carel Le Roux; Bartolome Burguera (Wiley, 2020)
Summary Setting Bariatric surgery is indicated for patients diagnosed with obesity and type 2 diabetes. Many patients achieve type 2 diabetes remission soon after bariatric surgery. Even though most maintain good glycemic control, remission is not maintained in all patients, and as a result, some patients may relapse. Type 2 diabetes relapse is common in patients who regain weight; weight regain is prevalent 1 to 2 years after surgery. Additional pharmacotherapy may be required to aid bariatric surgery in fostering weight loss and reducing blood glucose levels. Objectives The purpose of this clinical trial was to determine the effects of canagliflozin in participants who initially achieved type 2 diabetes remission but subsequently relapsed. Methods The double‐blinded, randomized, and prospective study recruited participants (n = 16) roughly 3 years after bariatric surgery. The participants were followed for 6 months. Results Body mass index (−1.24 kg/m2) and body weight (−3.7 kg) were significantly reduced with canagliflozin therapy versus placebo. There were improvements in body fat composition as denoted by reductions in android (−3.00%) and truncal (−2.67%) fat. Also, there were differences in blood glucose and hemoglobin A1C at 6 months. Conclusion After bariatric surgery, canagliflozin improved weight loss and glycemic outcomes in participants with type 2 diabetes. Canagliflozin also facilitated improvements in body fat composition.